Institutional change in the European Parliament: balancing legislative ethics and parliamentary independence. Issue 2 (3rd April 2019) - Cini, Michelle
ABSTRACT: Research on legislative ethics has shown how scandals often trigger ethics reform; yet, the content of the reform often differs from that of the scandal. Why is this the case? And if scandals don't explain legislative ethics reform outcomes, then what does? If not this kind of external shock, then what factor(s) shape legislative reform outcomes? These questions provide the point of departure for a case study of the European Parliament's 2011 ethics reform. Drawing from the legislative ethics literature and from recent theories of institutional change, the article examines the impact of the scandal that initiated the reform, the interests and strategies of reform agents who wanted a quick reform process that would not undermine the EP's independence; and the institutional order in which those actors were embedded. It argues that an institutional logics perspective offers a convincing and comprehensive account of EP ethics reform, and suggests a new analytical framework that might be used by researchers in future research on legislative ethics.